KEDUDUKAN MASLAHAH DAN UTILITY DALAM KONSUMSI (MASLAHAH VERSUS UTILITY) - Aisa Manilet (IAIN Ambon, 2017)
Requirement in Islam consists of dharuriyat needs, hajiyat, and tahsiniyat. The third is the need to have priorities that must be accomplished, and can not be postponed. In practice consumption, sometimes difficult to distinguish between needs (hajjah) with the desire (raghbah). Consumption aims to maximize maslahah, not satisfaction. Maslahah is good that one feels along the other side. While the utility is the satisfaction felt by someone who could be contradictory to the interests of others. So, maslahah and utilities alike the goal and can be achieved both by not bringing harm. Islamic consumer behavior based on rationality enhanced and integrate faith and truth that goes beyond human rationality is limited based on the Qur'an and Sunnah. Islam gives the concept of satisfying needs accompanied by moral force, without distress and the harmonious relationship among men. Keywords: maslahah, utility, consumption